Avaliação agronômica do antúrio irrigado com água de reuso - Saziki, Camilla Yuri Nishimura (Universidade Federal de São Carlos, 2023)
The aim of this study was to evaluate the effect of using treated domestic sewage from the Sewage Treatment Station (ETE) at CCA/UFSCar – Araras as an alternative source to commercial nutrient solutions in the cultivation of anthurium (Anthurium andraeanum cv. Sumi), using 3 treatments (TA: drinking water + mineral fertilizers; TR: reuse water; TRA: reuse water + supplementation with mineral fertilizers), through the collection of data on the total chlorophyll index and biometric measurements, namely stem size, of the largest leaf, spadix, spathe length, plant height, number of flowers and leaves. The experimental design was in randomized blocks, with four replications, and the data were submitted to analysis of variance, and determined by the F test, the means were compared by the Tukey test. The use of reuse water (RT) showed lower values ​​in the total chlorophyll index, and its biometric measurements were lower when compared to the other treatments. The TRA treatment did not present a significant difference in the biometric measurements, when compared with the TA treatment, but it presented a lower chlorophyll index when compared to the same. In this way, the use of reuse water complemented with mineral fertilizers can be a viable alternative option for the cultivation of anthurium.
Agronomic evaluation of anthurium irrigated with reuse water
Keywords: Cor; Medidas biométricas; Fertirrigação; Águas residuais; Color; Biometric measurements; Fertirrigation; Residual waters; CIENCIAS AGRARIAS::AGRONOMIA